Single nucleotide polymorphisms in the multidrug resistance gene 1 (ABCB1): effects on its expression and clinicopathological characteristics in breast cancer patients - Vaclavikova, Radka; Nordgard, Silje H; Alnaes, Grethe I G; Hubackova, Miluse; Kubala, Eugen; Kodet, Roman; Mrhalova, Marcela; Novotny, Jan; Gut, Ivan; Kristensen, Vessela N; Soucek, Pavel (Pharmacogenetics and genomics, 2008)
OBJECTIVES: Resistance of tumor cells to multiple cytostatic agents is one of the major impediments of successful cancer chemotherapy. A large part of resistance of tumors to chemotherapy is caused by the ABC transporter P-glycoprotein encoded by the ABCB1 gene. The main aim of this study was to assess the prognostic value of ABCB1 genotype and phenotype in breast cancer. METHODS: Six ABCB1 single nucleotide polymorphisms (SNPs) were determined in 90 Czech breast cancer patients by a novel method that allows simultaneous assessment of multiple polymorphisms on a single electronic microarray. Expression levels of ABCB1 were quantified in tumor and nontumor samples of breast cancer patients by real-time PCR. T-test, analysis of variance and Fisher's exact test were used to analyze the effect of ABCB1 polymorphisms on ABCB1 expression levels and for the analysis of associations between ABCB1 expression, genotype and clinical and pathological characteristics. RESULTS: ABCB1 was expressed in 98.9% of the tumor and in 97.5% of the nontumor samples. ABCB1 was downregulated in 79.5% of tumors compared with the nontumor samples. No significant correlation was observed between ABCB1 mRNA expression levels and clinical and pathological characteristics. High frequencies of the variant alleles in ABCB1 exon 12 (1236C>T, 38.3%) and exon 26 (3435C>T, 54.0%) were observed. Individuals with variant alleles in exons 12 and 26 had significantly lower ABCB1 expression levels in their tumors. SNPs in exons 12 and 26 also correlated with estrogen receptor status of patients. CONCLUSION: ABCB1 SNPs may affect function of P-glycoprotein by influencing the expression level and modify breast cancer prognosis.
Keywords: Receptors, Estrogen; regulace genové exprese u nádorů; dospělí; Drug Resistance, Neoplasm; mnohočetná léková rezistence; nádory prsu; Base Sequence; Oligonucleotide Array Sequence Analysis; Female; polymerázová řetězová reakce; Adult; Polymerase Chain Reaction; ženské pohlaví; farmakogenetika; jednonukleotidový polymorfismus; Gene Expression Regulation, Neoplastic; RNA nádorová; Gene Frequency; lidé; P-glykoprotein; ATP Binding Cassette Transporter, Subfamily B; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; Polymorphism, Single Nucleotide; Breast Neoplasms; chemorezistence; ATP Binding Cassette Transporter, Subfamily B, Member 1; DNA primery; messenger RNA; receptory pro estrogeny; Drug Resistance, Multiple; frekvence genu; prognóza; RNA, Messenger; P-glykoproteiny; Aged; sekvence nukleotidů; Pharmacogenetics; alely; Prognosis; RNA, Neoplasm; Alleles; DNA Primers; lidé středního věku; senioři; Middle Aged; Humans